2009
DOI: 10.1111/j.1399-3062.2009.00400.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of conventional and molecular detection of respiratory viruses in hematopoietic cell transplant recipients

Abstract: Background-Sensitive detection of respiratory viruses is important for early diagnosis of infection in patients following hematopoietic cell transplantation (HCT). To evaluate the relative sensitivity of respiratory virus detection in specimens from HCT recipients, we compared the results of conventional and quantitative molecular methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
112
3
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(121 citation statements)
references
References 18 publications
(35 reference statements)
5
112
3
1
Order By: Relevance
“…The observation of different techniques results showed that molecular methods had a superior detection rate when compared with immunofluorescence, mainly in samples of patients with three days of symptoms onset or more, as expected [13]. Indeed, the performance of qPCR was even better than the capacity of detection by PCR, particularly in cases of decreased viral shedding, as demonstrated with the comparison of viral loads, lower in those samples that could not have HRSV detected by DFA or by PCR.…”
Section: Discussionsupporting
confidence: 58%
“…The observation of different techniques results showed that molecular methods had a superior detection rate when compared with immunofluorescence, mainly in samples of patients with three days of symptoms onset or more, as expected [13]. Indeed, the performance of qPCR was even better than the capacity of detection by PCR, particularly in cases of decreased viral shedding, as demonstrated with the comparison of viral loads, lower in those samples that could not have HRSV detected by DFA or by PCR.…”
Section: Discussionsupporting
confidence: 58%
“…Viral isolation by conventional culture is the "gold standard" for diagnosis of RSV infection; however, it may take up to one week to finalize the culture and it has a low sensitivity. 11,12 Rapid diagnosis of RSV infection can be made by direct antigen testing on clinical specimens (ie, direct immunofluorescence staining), shell vial culture technique, which provides results within 48 hours, with a sensitivity of 93% and a specificity of 97%, 13 and by real-time polymerase chain reaction assays for detection of RSV RNA with a higher sensitivity and specificity. 11,12 HSCT recipients with influenza-like symptoms (ie, runny nose, fever, nasal congestion, sore throat, and cough) during the cold season should be tested for RSV and other respiratory viruses.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Rapid diagnosis of RSV infection can be made by direct antigen testing on clinical specimens (ie, direct immunofluorescence staining), shell vial culture technique, which provides results within 48 hours, with a sensitivity of 93% and a specificity of 97%, 13 and by real-time polymerase chain reaction assays for detection of RSV RNA with a higher sensitivity and specificity. 11,12 HSCT recipients with influenza-like symptoms (ie, runny nose, fever, nasal congestion, sore throat, and cough) during the cold season should be tested for RSV and other respiratory viruses. At our institution, we only screen symptomatic patients for respiratory viruses by obtaining nasal washes that are submitted for direct immunofluorescence antigen detection for RSV and influenza virus on the clinical specimen in addition to shell vial cultures.…”
Section: Introductionmentioning
confidence: 99%
“…2 The diagnostic gold standard is viral culture, however, detection of viral RNA in respiratory specimens by reverse transcription PCR represents a faster and more sensitive approach. 3 Although RSV is usually a self-limiting disease causing only mild symptoms of upper respiratory tract infection disease (URTID) or no symptoms at all, 4 it may be associated with severe LRTID in elderly or immunocompromised adults. 5,6 Morbidity and mortality rates reported in the literature are heterogeneous, the relevance of RSV infections in terms of outcome for patients undergoing autologous or allogeneic SCT ranging from none 7,8 to a mortality rate of up to 78%.…”
Section: Introductionmentioning
confidence: 99%